Agitator Design for Gas-Liquid Fermenters and Bioreactors - Benz, Gregory T (John Wiley & Sons, 2021)
This book delivers a concise treatment and explanation of how to design mechanically sound agitation systems that will perform the agitation process function efficiently and economically. The book covers agitator fundamentals, impeller systems, optimum power and air flow at peak mass transfer calculations, optimizing operation for minimum energy per batch, heat transfer surfaces and calculations, shaft seal considerations, mounting methods, mechanical design, and vendor evaluation. The accomplished author has created a practical and hands-on tool that discusses the subject of agitation systems from first principles all the way to implementation in the real world. Step-by-step processes are included throughout the book to assist engineers, chemists, and other scientists in the design, construction, installation, and maintenance of these systems.